INTEGRASI NILAI-NILAI TOLERANSI DALAM KURIKULUM PAI DI SMA - Nurul Mubin; Anwar Sa’dullah; Devi Wahyu Ertanti (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
Indonesia is one of the countries known and praised for its diversity which is very rich in ethnicity, race, customs, ethnicity, culture, language and religion. As a nation that has a lot of diversity and diversity in it, it is vulnerable to cause social conflicts and conflicts in the name of religion. Creating harmony, harmony, peace and national unity requires values that will be created as shared values and implemented in everyday life. This value is a value that is issued to answer any challenges and social and religious problems that exist. Related to this as one of the education and community empowerment more specifically about this learners, the values needed to be integrated in the 2013 curriculum as an educational concept that will be implemented in schools at the top (high school). The value of this learning will be internalized in the form of a learning process in every level of education in high school. More specifically, the value of this revision must be integrated in Islamic religious education subjects in accordance with the title of the research to be approved.